2018
DOI: 10.1016/j.ejvs.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Femoral Artery Closure with the FemoSeal Device After Cerebral Thrombectomy Using an 8 French Sheath

Abstract: The use of the FemoSeal device to close an 8F access sheath puncture site is feasible and safe, with a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…The FemoSeal VCD is intended for CFA retrograde approach hemostasis, where it has been proved to be safe and effective with vascular sheaths sized up to 8 Fr. 5,[9][10][11] The low rate (7%) and grading (1 and 2 based on CIRSE classification system for complications) 13 of adverse events observed in our study, combined with the high technical success rate (100%) in an unselected group of patients treated in daily routine, suggest high safety and efficacy of FemoSeal VCD in antegrade CFA puncture site hemostasis when using vascular sheaths ranging from 5 to 8 Fr. Therefore, FemoSeal VCD could be considered as a firstline hemostasis strategy in such cases.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The FemoSeal VCD is intended for CFA retrograde approach hemostasis, where it has been proved to be safe and effective with vascular sheaths sized up to 8 Fr. 5,[9][10][11] The low rate (7%) and grading (1 and 2 based on CIRSE classification system for complications) 13 of adverse events observed in our study, combined with the high technical success rate (100%) in an unselected group of patients treated in daily routine, suggest high safety and efficacy of FemoSeal VCD in antegrade CFA puncture site hemostasis when using vascular sheaths ranging from 5 to 8 Fr. Therefore, FemoSeal VCD could be considered as a firstline hemostasis strategy in such cases.…”
Section: Resultsmentioning
confidence: 58%
“…Anyway, our complication rate was comparable with that reported in literature for FemoSeal or other VCDs or MC, while our technical success (100%) was even hig her. [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][18]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and feasibility of this VCD on retrograde femoral artery access have been investigated and verified in previous studies [1][2][3][4][5][6][7][8]. A recent article showed that the device could also be safely used even for anterograde femoral artery access [9].…”
Section: Introductionmentioning
confidence: 72%
“…A r t i c l e compression was followed when technical failure was brought out in many reviews [1][2][3][4]6,7]. Even though the remarkable event has not been found after following manual compression in some studies [4][5][6][7], large hematomas were found in 36% of technical failure cases according to one large-scale survey, CLOSE-UP study [2]. A clear description of the result of technical failure cannot be found in the ISAR-CLOSURE study, another large-scale study [1].…”
Section: A C C E P T E Dmentioning
confidence: 99%